The Notion of Urban Cultural Landscape Concept From Landscape Architecture Perspective - Dini Rosmalia; Widjaja Martokusumo (Jurnal Lanskap Indonesia, 2012)
Urban cultural landscape is a concept considered as new and still raises many arguments among scholars. This concept comes from terms of cultural landscape and first was revealed in 1925 by Sauer, a Geographer. Then this term has evolved to be a concept of urban cultural landscape after finding many countries in the world are interesting to propose their historic cities as a World Heritage Cultural Landscape. Currently, some researchers from geography, anthropolo-gy, economics, architecture and landscape architecture have tried to reveal the concept. However, generally the description of their concept is more in processing or exploring the establishment elements of urban cultural landscape, so as can be seen that the concept is not comprehensive yet and still partial in accordance with the scientific background. Therefore, this paper aims to reveal the concept of urban cultural landscape from different disci-plines to gain a comprehensive one. And to support the establishment of the concept, the paper uses a case study, which is Cirebon city as it is one of the unique and historic cities in Indonesia. The city has been established since 15th century. The establishment has been affected by social, cultural, political and economic impacts from various periods of rules (Sultanate Cerbon, Dutch Colonial and the Republic of Indonesia).of rule (Sultanate Cerbon, Dutch Colonial and the Republic of Indonesia). Keywords: Cirebon city, landscape elements, urban components